(Post)colonial Theology in South Africa? A conversation with recent South African theology at the forefront of the decolonial turn - Wessels , Wessel (Stellenbosch Theological Journal, 2022)
This article endeavours a preliminary dialogue with theologies which seriously and explicitly contemplate the decolonial turn. As decolonial and postcolonial become important concepts for framing the context, questions must be asked with regards to the meaning(s), grounds for theologising and undercurrents of the conversations on these subjects. There is no doubt that the current theological direction which seriously consider decolonial and postcolonial thought will influence the future of theology. However, the framing, interpretation, and contextual framing of decolonial and postcolonial thought cannot go without serious interrogation from a wide variety of voices for the future of theology in South Africa. In this sense, this article hopes for endeavours of contemplating the framing of theological discourse within the concepts of decolonial and postcolonial.